2004
DOI: 10.1016/j.jcrs.2004.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Reasons patients recommend laser in situ keratomileusis

Abstract: Categories of reasons for recommending LASIK to others were similar to reasons given by patients for seeking LASIK. Some patients who reported dissatisfaction with their vision said they would recommend LASIK, suggesting that recommendation of LASIK to others is not necessarily a measurement of the quality of a patient's vision after LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…[3][4][5][6] Patient satisfaction has been shown to remain high, also beyond the initial 6-month follow-up period. 26 Our study likewise showed an excellent medical outcome with a good predictability and 86.8% of eyes within G0.5 D and 97.0% within G1.0 D from emmetropia. The mean score for the overall satisfaction was 4.10 G 0.71 on a scale of 0 to 5 (a score of 5 meaning that the patient was totally satisfied).…”
Section: Discussionsupporting
confidence: 76%
“…[3][4][5][6] Patient satisfaction has been shown to remain high, also beyond the initial 6-month follow-up period. 26 Our study likewise showed an excellent medical outcome with a good predictability and 86.8% of eyes within G0.5 D and 97.0% within G1.0 D from emmetropia. The mean score for the overall satisfaction was 4.10 G 0.71 on a scale of 0 to 5 (a score of 5 meaning that the patient was totally satisfied).…”
Section: Discussionsupporting
confidence: 76%
“…However, the post-operative pain associated with PRK has resulted in most patients recommending LASIK 1314. LASIK continues to be the preferred procedure by the majority of refractive surgeons 1011.…”
Section: Discussionmentioning
confidence: 99%
“…José Benítez-del-Castillo (San Carlos University Hospital, Madrid, Spain), discussed the emergence of dysfunctional tear syndrome following laser in situ keratomileusis (LASIK), which leads to dissatisfaction for both patients and surgeons 68. Decrease in tear secretion and corneal sensitivity after LASIK leading to OSD has been reported, and corneal sensitivity recovery using non-contact esthesiometry was not reached in many cases until 54 months after surgery 69.…”
Section: Osd After Refractive Surgerymentioning
confidence: 99%